(untitled) (Anclajes, 2019)
A body is full of other bodies. Both the erotic experience, as the religious and the poetic one, give an account of that desiring desire that allows us to dilute the edges of individuality in order to advance towards something that is beyond itself. The sonnets and tenths that make up a fleeting and disguised witness (1985) by the Cuban Severo Sarduy, to whom this article is dedicated, ―, stretch to the maximum the foundational images of Spanish mysticism to give an account of that dissolving experience where what is practiced is not "to be otherwise" but "another way to be".